2016
DOI: 10.17795/semj38677
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Burden of Inappropriate Admissions to Intensive Care Units of Shahid Faghihi and Nemazee Hospitals of Shiraz, Iran, 2014

Abstract: Background: Investigating the conditions and the appropriateness of admission of patients in hospitals is an important issue which can improve the efficiency of health care delivery. Intensive care unit (ICU) is important due to applying expensive financial sources; therefore, its efficient application is of great priority. In this regard, the current study aimed to determine the financial burden of inappropriate admissions in internal intensive care units (IICUs). Methods: It was a cross-sectional study condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 13 publications
1
11
1
Order By: Relevance
“…In another study by Soria-Aledo et al to estimate inappropriate admissions employing AEP, this rate was equal to 7.4% (1). Several other investigations that did not use AEP for inappropriate admission estimation reported higher rates (14% -24%) than the current study (15,(20)(21)(22)(23). For instance, this rate was reported as 22% in a study by Eriksen et al in Norway (21).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In another study by Soria-Aledo et al to estimate inappropriate admissions employing AEP, this rate was equal to 7.4% (1). Several other investigations that did not use AEP for inappropriate admission estimation reported higher rates (14% -24%) than the current study (15,(20)(21)(22)(23). For instance, this rate was reported as 22% in a study by Eriksen et al in Norway (21).…”
Section: Discussioncontrasting
confidence: 53%
“…In addition, the results of the study indicated that gender had no effect on the rate of inappropriate admission and days of hospital stay. Some studies also showed similar results (23,31); however, some other studies reported opposite results in this respect (25,32). The insurance state of patients had no effect on the prob-ability of inappropriate admission but had effects on inappropriate hospitalization.…”
Section: Discussionmentioning
confidence: 81%
“…Unnecessary hospitalization increases patient's costs, reduces the access of critically ill patients to existing resources, and increases the risk of hospital infections in hospitalized patients. Hence, examining the conditions for hospital admission and its appropriateness is one of the important issues that can improve the efficiency of hospitals . Furthermore, unnecessary presence of patients in hospitals may cause the inactivity of the community workforce and bring about related harm, occupational constraints, and negative emotional and psychological effects to the families…”
Section: Introductionmentioning
confidence: 99%
“…Hence, examining the conditions for hospital admission and its appropriateness is one of the important issues that can improve the efficiency of hospitals. 7 Furthermore, unnecessary presence of patients in hospitals may cause the inactivity of the community workforce and bring about related harm, occupational constraints, and negative emotional and psychological effects to the families. 8 Therefore, examining the conditions for hospital admission and its appropriateness, and continuous investigation of hospital services are important issues that can improve resource productivity, service quality, and hospital efficacy.…”
mentioning
confidence: 99%
See 1 more Smart Citation